2022
DOI: 10.1140/epjc/s10052-022-10718-x
|View full text |Cite
|
Sign up to set email alerts
|

The applicability of hydrodynamics in heavy ion collisions at $$\sqrt{s_\mathrm{NN}}$$ = 2.4–7.7 GeV

Abstract: To assess the degree of equilibration of the matter created in heavy-ion reactions at low to intermediate beam energies, a hadronic transport approach (SMASH) is employed. By using a coarse-graining method, we compute the energy momentum tensor of the system at fixed time steps and evaluate the degree of isotropy of the diagonal terms and the relative magnitude of the off-diagonal terms. This study focuses mostly on Au+Au collisions in the energy range $${\sqrt{s}_\mathrm{NN}}$$ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 93 publications
0
1
0
Order By: Relevance
“…Though the relaxation time is predicted to be smaller than the interpenetration time [28], the emission of dileptons in the very early stages of collisions is often not considered because of this uncertainty. On the other hand, a recent study has shown that shortly after interpenetration, the systems described do reach a state of local isotropy and equilibrium, and the assumption of a near-hydro T μ ν is justified [64]. In addition to extracting the local density and temperature, the coarse-graining procedure allows the local densities of π and ρ mesons and Δ baryons to be determined, which can be used to check whether a system is in local chemical equilibrium.…”
Section: Coarse Grainingmentioning
confidence: 99%
“…Though the relaxation time is predicted to be smaller than the interpenetration time [28], the emission of dileptons in the very early stages of collisions is often not considered because of this uncertainty. On the other hand, a recent study has shown that shortly after interpenetration, the systems described do reach a state of local isotropy and equilibrium, and the assumption of a near-hydro T μ ν is justified [64]. In addition to extracting the local density and temperature, the coarse-graining procedure allows the local densities of π and ρ mesons and Δ baryons to be determined, which can be used to check whether a system is in local chemical equilibrium.…”
Section: Coarse Grainingmentioning
confidence: 99%